Aquatic fungal diversity assessment through metagenomics is still limited to current databases - Anushree Sanyal; Mariana Kluge; Miguel Angel Redondo; Moritz Buck; Maliheh Mehrshad; Sarahi L. Garcia; Stefan Bertilsson; Sari Peura (Limnology and Oceanography, 2025)
Fungi play essential roles across ecosystems, yet their diversity in aquatic environments remains poorly understood compared to terrestrial systems. To address this gap, we analyzed metagenomes from 26 lakes in the boreal and subarctic zones, along with one tropical reservoir, to characterize fungal and fungal‐like (Oomycota) community structure. We also examined environmental factors shaping these communities. Most variation in fungal composition was explained by lake identity, depth layer, and season, with total organic carbon as a significant explanatory variable. Despite geographic and time differences, dominant fungal phyla, orders, and genera were largely consistent across all lakes. However, genus‐level variation indicated distinct community compositions likely influenced by differences in carbon substrate availability. Attempts to classify metagenomic reads down to the species level—illustrated here through the well‐characterized oomycete genus Phytophthora —were constrained by the limited taxonomic resolution of current reference databases. While metagenomics offers powerful means to investigate entire microbial communities, our results underscore a persistent bottleneck: the insufficient representation of aquatic eukaryotic genomes in public databases.

Differences in community structuring among planktonic bacterial and micro-eukaryotic phyla in Chilean freshwater lakes - Maxime Sweetlove; Bjorn Tytgat; Evelien Van de Vyver; Elie Verleyen; Sofie D‘hondt; Dagmar Obbels; Moritz Buck; Roberto Urrutia; Stefan Bertilsson; Wim Vyverman (Limnologica, 2025)

Impact of climate change on the kelp Laminaria digitata – simulated Arctic winter warming - Moritz Trautmann; Inka Bartsch; Margot Bligh; Hagen Buck-Wiese; Jan-Hendrik Hehemann; Sarina Niedzwiedz; Niklas Plag; Tifeng Shan; Kai Bischof; Nora Diehl (Frontiers in Marine Science, 2024)
The Arctic is seasonally exposed to long periods of low temperatures and complete darkness. Consequently, perennial primary producers have to apply strategies to maximize energy efficiency. Global warming is occurring in the Arctic faster than the rest of the globe. The highest amplitude of temperature rise occurs during Polar Night. To determine the stress resistance of the ecosystem-engineering kelp Laminaria digitata against Arctic winter warming, non-meristematic discs of adult sporophytes from Porsangerfjorden (Finnmark, Norway) were kept in total darkness at 0°C and 5°C over a period of three months. Physiological variables, namely maximum quantum yield of photosynthesis (F v /F m ) and dry weight, as well as underlying biochemical variables including pigments, storage carbohydrates, total carbon and total nitrogen were monitored throughout the experiment. Although all samples remained in generally good condition with F v /F m values above 0.6, L. digitata performed better at 0°C than at 5°C. Depletion of metabolic products resulted in a constant decrease of dry weight over time. A strong decrease in mannitol and laminarin was observed, with greater reductions at 5°C than at 0°C. However, the total carbon content did not change, indicating that the sporophytes were not suffering from “starvation stress” during the long period of darkness. A decline was also observed in the accessory pigments and the pool of xanthophyll cycle pigments, particularly at 5°C. Our results indicate that L. digitata has a more active metabolism, but a lower physiological and biochemical performance at higher temperatures in the Arctic winter. Obviously, L. digitata is well adapted to Arctic Polar Night conditions, regardless of having its distributional center at lower latitudes. Despite a reduced vitality at higher temperatures, a serious decline in Arctic populations of L. digitata due to winter warming is not expected for the near future.

Microbial communities mediating net methylmercury formation along a trophic gradient in a peatland chronosequence - Baolin Wang; Haiyan Hu; Kevin Bishop; Moritz Buck; Erik Björn; Ulf Skyllberg; Mats B. Nilsson; Stefan Bertilsson; Andrea G. Bravo (Journal of Hazardous Materials, 2023)

Oxygen‐deficient water zones in the Baltic Sea promote uncharacterized Hg methylating microorganisms in underlying sediments - Eric Capo; Elias Broman; Stefano Bonaglia; Andrea G. Bravo; Stefan Bertilsson; Anne L. Soerensen; Jarone Pinhassi; Daniel Lundin; Moritz Buck; Per O. J. Hall; Francisco J. A. Nascimento; Erik Björn (Limnology and Oceanography, 2022)
Human‐induced expansion of oxygen‐deficient zones can have dramatic impacts on marine systems and its resident biota. One example is the formation of the potent neurotoxic methylmercury (MeHg) that is mediated by microbial methylation of inorganic divalent Hg (Hg II ) under oxygen‐deficient conditions. A negative consequence of the expansion of oxygen‐deficient zones could be an increase in MeHg production due to shifts in microbial communities in favor of microorganisms methylating Hg. There is, however, limited knowledge about Hg‐methylating microbes, i.e., those carrying hgc genes critical for mediating the process, from marine sediments. Here, we aim to study the presence of hgc genes and transcripts in metagenomes and metatranscriptomes from four surface sediments with contrasting concentrations of oxygen and sulfide in the Baltic Sea. We show that potential Hg methylators differed among sediments depending on redox conditions. Sediments with an oxygenated surface featured hgc ‐like genes and transcripts predominantly associated with uncultured Desulfobacterota (OalgD group) and Desulfobacterales (including Desulfobacula sp.) while sediments with a hypoxic‐anoxic surface included hgc ‐carrying Verrucomicrobia, unclassified Desulfobacterales, Desulfatiglandales, and uncharacterized microbes. Our data suggest that the expansion of oxygen‐deficient zones in marine systems may lead to a compositional change of Hg‐methylating microbial groups in the sediments, where Hg methylators whose metabolism and biology have not yet been characterized will be promoted and expand.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Auxotrophy and intrapopulation complementary in the ‘interactome’ of a cultivated freshwater model community - Sarahi L. Garcia; Moritz Buck; Katherine D. McMahon; Hans‐Peter Grossart; Alexander Eiler; Falk Warnecke (Molecular Ecology, 2015)
Microorganisms are usually studied either in highly complex natural communities or in isolation as monoclonal model populations that we manage to grow in the laboratory. Here, we uncover the biology of some of the most common and yet‐uncultured bacteria in freshwater environments using a mixed culture from Lake Grosse Fuchskuhle. From a single shotgun metagenome of a freshwater mixed culture of low complexity, we recovered four high‐quality metagenome‐assembled genomes ( MAG s) for metabolic reconstruction. This analysis revealed the metabolic interconnectedness and niche partitioning of these naturally dominant bacteria. In particular, vitamin‐ and amino acid biosynthetic pathways were distributed unequally with a member of Crenarchaeota most likely being the sole producer of vitamin B12 in the mixed culture. Using coverage‐based partitioning of the genes recovered from a single MAG intrapopulation metabolic complementarity was revealed pointing to ‘social’ interactions for the common good of populations dominating freshwater plankton. As such, our MAG s highlight the power of mixed cultures to extract naturally occurring ‘interactomes’ and to overcome our inability to isolate and grow the microbes dominating in nature.